PEMODELAN STEADY STATE SISTEM PANAS BUMI DAERAH SUMBER AIR PANAS DIWAK-DERAKAN DENGAN MENGGUNAKAN SOFTWARE HYDROTHREM 2.2 - Aditya Firdaus; Udi Harmoko; Sugeng Widada (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
Steady State Modeling has been done hot springs Diwak-Derekan using Hydrotherm 2.2 software which aims to model numerically geothermal system Diwak-Derekan in Steady State conditions. The results form the output of Hydrothrem 2.2 Temperature Distribution and visualization of the data carried Temperature Distribution.Extent of the study area is 16 km x 16 km, where there is a buffer area in the outer portion of the study area. then made construction research area consisting of several slice and block research. Used topographic data using secondary data, and topographic data modeling made in accordance with the slice. Each slice of the construction area made initial research model that contains the physical parameters. Due to the limitations of the data parameters of physics, then some physical parameters of the data analogous to data from Mount Merapi and soil mechanics research data Diponegoro University Dam, physical parameters and the data is made in the form of program listings in the form of input for software Hydrothrem which Hydrotherm Software run the program until the year to 200,000 by year interval 10,000 years.The results of data visualization is seen that the temperature distribution for the data in the year to 80,000 and so no change is significant, this indicates that in the year to 80,000 already reached Steady State conditions. Khono (2000) said, geothermal system reach steady state condition between 200.000-500.000 years, its because using analogical data from Merapi Vulcano and ground mechanic Diponegoro University dam. Manifestations of geothermal systems around the emergence of hot water Diwak-Derekan a geothermal system associated with sediments. This is confirmed by studies based on the gravity method which is done around the study area, where there are faults trending down southwest - northeast parallel to Kali and Kali Jumbleng Klampok, where after a qualitative interpretation there are 4 layers of rock, where the top layer is sediment layer has a depth of about 3 km.Keywords: geothermal, fault, Distributions Temperature, geothermal systems, Steady State.